2019
DOI: 10.4314/ijbcs.v13i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and resistance profile of <i>Escherichia coli</i> and <i>Klebsiella pneumoniae</i> isolated from urinary tract infections in N'Djamena, Tchad

Abstract: Bacterial resistance to antibiotics is a worldwide problem. In Chad, statistical data are scarce. The reason why this study was undertaken from June 2014 to December 2016, to identify the main Enterobacteriaceae responsible for urinary tract infections and their susceptibility to antibiotics. Germs were isolated and identified by standard microbiology methods and tested with antibiotics according to Kirby-Bauer technique. Data collected was analyzed using Excel and Statistical Package for Social Sciences (SPSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
4
4
0
Order By: Relevance
“…and S. aureus (Table 2). These results corroborate those of previous studies conducted in Africa [23][24][25]. Many virulence and tness factors confer advantages to uropathogenic E. coli (UPEC) and K. pneumoniae (UPKP) in the host urinary tract.…”
Section: Discussionsupporting
confidence: 91%
“…and S. aureus (Table 2). These results corroborate those of previous studies conducted in Africa [23][24][25]. Many virulence and tness factors confer advantages to uropathogenic E. coli (UPEC) and K. pneumoniae (UPKP) in the host urinary tract.…”
Section: Discussionsupporting
confidence: 91%
“…Only carbapenem (imipenem) was effective against all tested strains in the β-lactam class. The absence of resistance to this antibiotic was previously reported by Yandai et al [32] in Chad and Kotb et al [33] in Egypt.…”
Section: Disk Diffusion Susceptibility Testingsupporting
confidence: 63%
“…Such prevalence is similar to 24.5% for E. coli and 18.4% for K. pneumoniae reported in an earlier study in Nigeria. 17 However, the prevalence of E. coli found in UTIs is significantly lower than those between 60% and 90% reported in Chad; 18 Madagascar; 19 Rwanda 20 and Morocco. 21 We found that urinary tract infections due to E. coli mainly affected women, which is in agreement with similar studies carried out in Cameroon 22 and Nigeria.…”
Section: Discussionmentioning
confidence: 85%
“…Similar resistance rates have been reported on an outpatient basis in West Africa, 26 Madagascar, 19 the Central African Republic 27 and Chad. 18 These high resistance rates could explain why aminopenicillins and carboxypenicillins are no longer recommended for the probabilistic treatment of UTIs. 28…”
Section: Discussionmentioning
confidence: 99%